Personality and smartphone addiction: the role of smartphone usage types as moderator among UTAR undergraduate students - Nurul Ain, Abd Rahim; Siah, Yih Huang; Tee, Xiang Yi (2018)
The present study explores the role of smartphone usage as mediator in the relationship between extroversion and smartphone addiction among UTAR undergraduate students. A total of 318 participants were recruited via purposive sampling in UTAR Kampar Campus. Data were collected using paper-and-pencil survey and online survey via Google Forms, which included items from International Personality Item Pool-Five Factor Model-50 (IPIP- 5-50), Process and Social Usage Scale and Smartphone Addiction Inventory scale (SPAI). The data were analysed using Statistical Package for Social Science (SPSS) statistical software 23th version. Results showed that there was a significant negative correlation between extroversion and process usage of smartphone, process usage positively correlated to smartphone addiction and extroversion was not correlated to smartphone addiction. Mediation analysis revealed that a complete mediation was found in the relationship between extroversion and smartphone addiction via process usage of smartphone. In contrast, social usage of smartphone did not act as the mediator in the association between extroversion and smartphone addiction. The results shed light on the underlying mechanism of how extroversion may lead to smartphone addiction. It also indicated that individuals shall pay attention to the process usage of smartphone as it acts as an underlying mechanism between extroversion and smartphone addiction. The utilisation of process usage of smartphone shall be reduced as it may lead to smartphone addiction which cause many adverse impacts.